Frontier markets for dummies - Graham, Gavin; Emid, Al (Hoboken, NJ : For Dummies, a Wiley brand, 2014)
Frontier markets are producing excellent returns for investors. This guide will help you discover the best approaches to investing in these up-and-coming global markets, maximizing returns, and diversifying your portfolio.
Introduction -- Getting started with frontier markets -- Examining issues affecting frontier market performance -- Approaching frontier market investments with savvy -- Making investment selections -- The part of tens -- Appendix: A quick survey of some emerging and frontier market countries.
Includes index.
Tặng
Keywords: Investments, Foreign -- Developing countries